2017
DOI: 10.1080/10942912.2017.1374290
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study on the effect of duck and hen egg albumens on proteolysis and gel property of sardine surimi

Abstract: The effects of duck and hen albumens at different levels (1%-4%, w/w) on proteolysis and gel properties of sardine (Sardinella albella) surimi were studied. The addition of both albumens into surimi resulted in the increases in breaking force and deformation, especially with increasing levels added (P < 0.05). Both albumens inhibited autolysis of surimi in a dose dependent manner as indicated by the lower TCA-peptide content and more retained myosin heavy chain and actin. Texture profile analysis showed that h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
40
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 29 publications
(40 citation statements)
references
References 29 publications
0
40
0
Order By: Relevance
“…Nevertheless, the band intensity of AC with MW of 43–44 kDa was noticeably increased with increasing amount of SDEAP (SDEAP‐4 and SDEAP‐5 samples). It was reinforced that ovalbumin in duck egg albumen (MW: 44 kDa) contributed to the increase in the aforementioned band intensity (Quan & Benjakul, ). Both AC and ovalbumin appeared as the same protein band.…”
Section: Resultsmentioning
confidence: 98%
See 3 more Smart Citations
“…Nevertheless, the band intensity of AC with MW of 43–44 kDa was noticeably increased with increasing amount of SDEAP (SDEAP‐4 and SDEAP‐5 samples). It was reinforced that ovalbumin in duck egg albumen (MW: 44 kDa) contributed to the increase in the aforementioned band intensity (Quan & Benjakul, ). Both AC and ovalbumin appeared as the same protein band.…”
Section: Resultsmentioning
confidence: 98%
“…SDEAP also contained serine protease inhibitors (5,975 kunits/g solid). SDEAP could therefore prevent proteolysis in surimi, thus alleviating gel softening induced by indigenous proteases (Quan & Benjakul, ). SDEAP had white color.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, Quan and Benjakul () reported that duck albumen containing high protease inhibitory activity could increase gel strength of sardine surimi. Thus, duck albumen was suggested to replace hen albumen to alleviate gel weakening caused by endogenous proteases (Quan & Benjakul, ).…”
Section: Introductionmentioning
confidence: 99%